Translating Early Modern Science (Volume 51) - Fransen, Sietske (Brill, 2017)
Translating Early Modern Science explores the roles of translation and the practices of translators in early modern Europe. In a period when multiple European vernaculars challenged the hegemony long held by Latin as the language of learning, translation assumed a heightened significance. This volume illustrates how the act of translating texts and images was an essential component in the circulation and exchange of scientific knowledge. It also makes apparent that translation was hardly ever an end in itself; rather it was also a livelihood, a way of promoting the translator's own ideas, and a means of establishing the connections that in turn constituted far-reaching scientific networks.